Chronic Kidney Disease Preventive Attitude, Practice, and Associated Factors among Type 2 DM Patients in Ethiopia: A Cross-Sectional Study - Addisu Dabi Wake MSc; Sena Babsa Dinsa BSc (SAGE Open Nursing)
Introduction Globally, chronic kidney disease (CKD) has emerged as one of the leading causes of mortality and it is one of a small number of noncommunicable diseases that have shown an increase in associated deaths over the past two decades. Chronic kidney disease affects approximately 50% of patients with type 2 diabetic mellitus (DM). Objective To determine CKD preventive attitude, practices, and associated factors among type 2 DM (T2DM) patients attending follow-up in a diabetic clinic at Asella Referral and Teaching Hospital. Methods Institutional based cross-sectional study was conducted at Asella Referral and Teaching Hospital among T2DM patients from December 23, 2021, to January 23, 2022. Data were entered into EpiData 4.2.00 and analyzed by Statistical Package for the Social Sciences version 23.0. Result A total of 216 study participants were included in to this study. The level of good preventive attitude and practice toward CKD among T2DM patients were 61.6% ( n  = 133, 95% CI: 55.6–68.0) and 54.6% ( n  = 118, 95% CI: 47.7–60.6), respectively. Age (50–59 years) (adjusted odds ratio [AOR] = 0.351, 95% CI: 0.125–0.988, p  = .047), married (AOR = 4.423, 95% CI: 1.366–14.314, p  = .013), urban residents (AOR = 0.321, 95% CI: 0.152–0.680, p  = .003), and governmental employed (AOR = 0.269, 95% CI: 0.076–0.954, p  = .042) were significantly associated with CKD preventive attitude. Formal education (AOR = 1.686, 95% CI: 1.416–5.502, p  = .043), an average monthly income of ≥8000 ETB (AOR = 4.048, 95% CI: 1.129–14.520, p  = .032), family history of CKD (AOR = 1.417, 95% CI: 1.231–7.136, p  = .045) were significantly associated with CKD preventive practice. Conclusion The level of good preventive attitude and practice toward CKD among T2DM patients was 61.6% and 54.6%, respectively. Age, marital status, residence, and occupation were significantly associated with good preventive attitude of T2DM patients. Whereas educational status, average monthly income, and duration since diagnosed with T2DM were significantly associated with good CKD preventive practice. Health educational program needs to occur to improve the preventive attitude and practice toward CKD among T2DM patients.